Developing a student attendance record system facilitates for class teachers to make evaluation / Munirah Mokhtar, M. Irwan and Mohd Najib Husain - Mokhtar, Munirah; Irwan, M.; Husain, Mohd Najib (2022)
This research took a different approach on students when introducing the use of a new attendance recording system to record student attendance. The problem statement highlights for previously the class teacher had a problem calculating the attendance of class students on a monthly basis. The workload of classroom teachers is increasing due to the many things that need to be recorded as a classroom teacher. The system that will be developed can help class teachers to record the first warning, second and then further action without having to calculate manually. The method introduced in this research is to develop a new system to support the existing system. Data of students from one school in Central Perak will be used as a study to obtain the results and then can be used for other schools in Malaysia. As a result, classroom teachers are able to generate attendance records for each of their students accurately, quickly and efficiently. The student report that can be generated will be used as evidence to be kept by the school administration and shown to the student's parents. This study helps the community, especially on behalf of teachers and school administration; it is very beneficial to them.